Study on the effects of different sterilization methods and storage conditions on milk quality - Khayrullin, Mars; Rebezov, Maksim (Food Science and Technology, 2023)
Milk is processed in different ways. Milk may be heated, frozen, or condensed as it is excreted in raw milk or in order to kill pathogenic microorganisms and increase shelf life. Its protein and fat content may change. Lactose is hydrolyzed, homogenized, cholesterol is removed, or fermented cultures are added to it, and its calcium levels are increased. Some special processing operations are performed to meet the consumer's needs and the specific market situation. Due to its characteristics such as relatively long shelf life, the use of UHT sterilized milk has always been associated with the suspicion among consumers that this type of milk contains preservatives or its nutritional value is greatly reduced by applying high temperatures. In this article, while briefly referring to the nutritional value of milk, the effect of pasteurization and sterilization heat on the milk components is compared. Milk is the only food known in nature that can meet the body's basic needs for nutrients in a balanced way. Milk contains a very valuable set of proteins, sugars, fats, various minerals, especially calcium and phosphorus, and a variety of vitamins. Due to its special composition, this valuable nutrient is a very suitable environment for the multiplication of pathogenic microorganisms and the transmission of diseases from animals to humans.